Penggunaan Nisan Arca: Wujud Pengaruh Budaya Pra-Islam pada Kompleks Makam Islam di Wilayah Etnis Bugis, Sulawesi Selatan - Purnamasari, Nurul Adliyah; Hasrianti; Sritimuryati; Suryaningsi, Tini (Penerbit BRIN (BRIN Publishing), 2024)
Abstract. The Use of Tombstone Statues: Pre-Islamic Cultural Influence in Islamic Cemetery Complexes in The Bugis Ethnic Region, South Sulawesi. Unlike several previous studies that focused on the discovery and distribution of tombstone statues in the Makassar ethnic region, this research specifically examines the influence of pre-Islamic culture on the use of tombstone statues in the Bugis ethnic area, including Barru, Bone, Pinrang, Sidrap, Enrekang, and East Luwu Regencies. The study was conducted with the desk study method, reviewing various literature sources that document the presence of tombstone statues in the Bugis ethnic region, including the research reports of Archaeological Center (Balai Arkeologi), scientific articles, books, theses, dissertations, technical study reports, conservation, and zoning report from the Cultural Heritage Preservation Office (Balai Pelestarian Cagar Budaya), as well as other online reference sources. This research reveals that the use of these tombstones was suspected to be the influence of pre-Islamic culture, which had developed strongly in the previous period. This is evidenced by the discovery of megalithic statues in several areas in South Sulawesi and its neighboring province in Central Sulawesi, which functioned as ceremonial media and representations of ancestral spirits. Keywords: Tombstone Statues, Bugis Ethnic, Islamic Cemetery, Pre-Islam Abstrak. Berbeda dengan beberapa penelitian sebelumnya yang fokus terhadap penemuan dan sebaran nisan arca di wilayah Etnis Makassar, penelitian ini secara khusus mengkaji pengaruh budaya pra-Islam terhadap temuan nisan arca pada kompleks makam Islam di wilayah Etnis Bugis, meliputi Kabupaten Barru, Bone, Pinrang, Sidrap, Enrekang dan Luwu Timur. Penelitian ini menggunakan metode desk study, dengan melakukan penelahaan berbagai sumber pustaka yang memuat kehadiran nisan arca di wilayah Etnis Bugis, baik itu pada laporan penelitian Balai Arkeologi, artikel ilmiah, buku, skripsi, tesis maupun disertasi, laporan studi teknis, penyelamatan, dan zonasi Balai Pelestarian Cagar Budaya, serta sumber referensi lainnya yang tersedia secara daring. Penelitian ini menghasilkan informasi bahwa penggunaan nisan arca di wilayah Etnis Bugis diduga sebagai pengaruh dari budaya pra-Islam yang telah berkembang kuat pada periode sebelumnya. Hal tersebut dapat dibuktikan melalui penemuan arca megalitik di beberapa wilayah di Sulawesi Selatan dan provinsi terdekatnya di Sulawesi Tengah yang berfungsi sebagai media upacara dan representasi roh nenek moyang. Kata kunci: Nisan Arca, Etnis Bugis, Makam Islam, Pra-Islam